MULTIKULTURALISME DALAM PERSPEKTIF ISLAM: PENGERTIAN, URGENSI, DAN ANALISIS - Eva Maya Sari; Nini Maswati; Muktar Asroni; Ansori Ansori; Iwan Aprianto (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2026)
ABSTRACT Indonesia's highly diverse society, characterized by differences in ethnicity, culture, language, and religion, continues to face challenges such as intolerance, social polarization, radicalism, and hate speech, indicating that diversity has not yet been managed inclusively. This condition highlights the need to examine multiculturalism from an Islamic perspective as a conceptual foundation for fostering harmonious social life. This study aims to analyze the concept of multiculturalism in Islam, examine its significance for plural societies, and explore the historical, theological, and contextual foundations supporting its implementation. This research employed a qualitative library research approach. Data were collected from the Qur'an, Hadith, academic books, and scholarly journal articles published between 2016 and 2026 and were analyzed using content analysis. The findings identified six major themes: the concept of multiculturalism, Islamic fundamental values, the significance of multiculturalism, historical perspectives, theological perspectives, and contemporary challenges. The study concludes that diversity is regarded as sunnatullah and should be managed through the principles of al-ta'aruf, al-tasamuh, al-'adalah, and ukhuwah insaniyah. Furthermore, the integrative analysis demonstrates that Islamic multiculturalism provides a relevant framework for strengthening religious moderation, social cohesion, and multicultural Islamic education in promoting a peaceful, inclusive, and just society. ABSTRAK Keberagaman masyarakat Indonesia yang ditandai oleh perbedaan suku, budaya, bahasa, dan agama masih dihadapkan pada berbagai persoalan seperti intoleransi, polarisasi sosial, radikalisme, dan ujaran kebencian yang menunjukkan belum optimalnya pengelolaan keberagaman secara inklusif. Kondisi tersebut menegaskan pentingnya kajian mengenai multikulturalisme dalam perspektif Islam sebagai landasan konseptual dalam membangun kehidupan masyarakat yang harmonis. Penelitian ini bertujuan menganalisis konsep multikulturalisme dalam perspektif Islam, mengkaji urgensinya bagi masyarakat plural, serta menelaah landasan historis, teologis, dan kontekstual yang mendukung penerapannya. Penelitian menggunakan pendekatan kualitatif dengan jenis library research. Data diperoleh dari Al-Qur'an, hadis, buku, dan artikel ilmiah periode 2016–2026, kemudian dianalisis menggunakan content analysis. Hasil penelitian mengidentifikasi enam tema utama, yaitu konsep multikulturalisme, nilai dasar Islam, urgensi multikulturalisme, perspektif historis, perspektif teologis, dan tantangan kontemporer. Temuan menunjukkan bahwa keberagaman dipandang sebagai sunnatullah yang dikelola melalui prinsip al-ta'aruf, al-tasamuh, al-'adalah, dan ukhuwah insaniyah. Analisis integratif juga menegaskan bahwa multikulturalisme Islam memiliki relevansi dalam memperkuat moderasi beragama, kohesi sosial, serta pendidikan Islam multikultural untuk mewujudkan masyarakat yang damai, inklusif, dan berkeadilan.